OPTIMIZING EMPLOYEE RECRUITMENT PROCESS IN THE EDUCATION BUSINESS THROUGH CHATGPT IMPLEMENTATION - Sulaeman, Moh. Muklis; Nurcholidah, Lilik; Handayati, Ratna; Wibowo, Sandi Nasrudin (PT. LITERASI SAINS NUSANTARA, 2024)
Educational businesses, such as schools, colleges, and training institutions, have an increasing need to recruit quality employees who have the potential to fill various positions, ranging from teaching staff to administrative personnel. An efficient and effective recruitment process is crucial to ensure that educational institutions can maintain their quality standards and meet the educational needs of the community effectively. This research aims to explore how ChatGPT can be optimized to enhance the employee recruitment process in the education business. The study adopts a qualitative literature review approach, utilizing data from Google Scholar spanning from 2016 to 2023. This approach involves an in-depth analysis of various articles, journals, and related scholarly works published during this period. The study findings indicate that optimizing the employee recruitment process in the education business through ChatGPT implementation offers significant potential to enhance efficiency, effectiveness, and overall user experience. By leveraging artificial intelligence to provide quick responses, conduct initial interviews, and offer personalized experiences to applicants, ChatGPT can be a valuable tool for recruitment teams in selecting the most suitable candidates for available positions.